The Relationship between Servqual, Word of Mouth and the Selection of Private Universities in Indonesia - ., Purwantoro; Nizam, Nurul Zarirah (International Journal of Membrane Science and Technology, 2023)
The purpose of this study is to predict the relationship between service quality, word of mouth, and the selection of private universities. This research uses a quantitative approach. Data collection was carried out by distributing questionnaires to 353 respondents using google Forms. The data were statistically analyzed using the SmartPLS. The results showed that part there was a significant influence of Functional Quality, and image on the variables of college selection, and word of mouth. There are Technical Quality variables that have no effect on the variables of college selection and word of mouth. The results also show that the research model is good for predictors because more information can explain the R square of 0.796.